Implication of Multi-National Corporations (MNC’s) and Commercial Tea Plantation Agriculture on the Small Scale Farmers of Kericho in Kenya, 1963 -2010. - Peter, Kirui; Koech, Paulo K (Advances in Social Sciences Research Journal, 2022)
The introduction of tea as a cash crop in Kericho revolutionised farming among the Kipsigis of Kericho. While the independence of Kenya in 1963 was expected to come along with economic empowerment and freedom among its people, many still struggle to meet their daily needs and live below the poverty line. For Kericho residents, MNC’s continued their domination in plantation tea farming at the expense of the local communities who are wallowing in poverty. Although MNC’s contribute in the provision of social services to the local community as part of their corporate social responsibility, this assistance is a drop in the ocean considering the massive capital and technology that these corporations wield and which have been instrumental in relegating the small scale farmers to the periphery and creating dependency. This study explored the implication of MNC’s engaged in plantation tea farming in Kericho District (presently Kericho County) on local peasant farmers.